GERMAN COMPANIES IN ARGENTINA DURING THE SECOND PHASE OF INDUSTRIALIZATION BY IMPORTS SUBSTITUTION (1960-1970) - Rossi , Ignacio Andrés (2022)
The role of foreign companies in the Argentine economy has been arousing the interest of historians in recent years. The most recent contributions, although of vital importance, have focused on more global examinations than on specific national cases. In this paper we propose to analyze the role of foreign German companies in the Argentine economy between the years 1960 and 1970. From a database prepared by a team of Argentine researchers, comparative variables such as the volume of capital, the specific branches and the number of firms registered between both decades. A relative importance of German capital has been observed during the stage of the second cycle of foreign investment and the second phase of Import Substitution Industrialization (ISI); but some significant nuances were also established between large, medium and small firms in regards to greater diversification such as the impact of the volume of capital.